Tourism in Malaysia: an empirical study on socio-economic and environmental impacts - Karim, A.H.M Zehadul; Md. Noon, Hazizan; Mohd Noor, Noor Azlan; Mohamad Diah, Nurazzura (Partridge Singapore, 2016)
As a pluralistic nation, Malaysia consists of diverse ethnic groups of people with various cultures that integrate harmonious and peaceful living in a politically stable and wonderfully rich environmental setting. Due to such unique features, people from abroad become largely attracted to this land and thus frequently arrive here as visitors and tourists. There are tremendous amounts of attractions for the visitors and tourists, and people from various backgrounds arrive to stay here temporarily, generating around RM65 billion in foreign earnings, adding to its national coffer every year. Nevertheless, tourism also causes a major negative effect in which the local culture may be assimilated into the alien norms and behaviors through the continuous process of acculturation. Due to day-to-day interactions with the tourists and visitors, many sociocultural impacts have affected local values, which contextually require to be redefined. This book analyzes critically the sociocultural and environmental impacts of tourism in Malaysia, having collected both qualitative and quantitative data at the empirical level of investigation.